Clinical evaluation of the Multimapping technique for simultaneous myocardial T1 and T2 mapping - Jarkman, Charlotta; Carlhäll, Carl-Johan; Henningsson, Markus (Frontiers in Cardiovascular Medicine, 2022)
The Multimapping technique was recently proposed for simultaneous myocardial T1 and T2 mapping. In this study we evaluate its correlation with clinical reference mapping techniques in patients with a range of cardiovascular diseases (CVD), compare image quality and inter- and intra-observer repeatability. Multimapping consists of a ECG-triggered, 2D single-shot bSSFP readout with inversion recovery and T2 preparation modules, acquired across 10 cardiac cycles. The sequence was implemented at 1.5T and compared to clinical reference mapping techniques, Modified Look-Locker inversion recovery (MOLLI) and T2 prepared bSSFP with four echo times (T2bSSFP), and compared in 47 patients with CVD (of which 44 were analyzed). In diseased myocardial segments (defined as presence of late gadolinium enhancement) there was a high correlation between Multimapping and MOLLI for native myocardium T1 (r2=0.73), ECV (r2=0.91) and blood T1 (r2=0.88), and Multimapping and T2bSSFP for native myocardial T2 (r2=0.80). In healthy myocardial segments a bias for native T1 (Multimapping=1116±21 ms, MOLLI=1002±21, P<0.001), post-contrast T1 (Multimapping=479±31 ms, MOLLI=426±27 ms, 0.001), ECV (Multimapping=21.5±1.9%, MOLLI=23.7±2.3%, P=0.001) and native T2 (Multimapping=48.0±3.0 ms, T2bSSFP=53.9±3.5 ms, P<0.001) was observed. The image quality for Multimapping was scored as higher for all mapping techniques (native T1, post-contrast T1, ECV and T2bSSFP) compared to the clinical reference techniques. The inter- and intra-observer agreement was excellent (intraclass correlation coefficient, ICC>0.9) for most measurements, except for inter-observer repeatability of Multimapping native T1 (ICC=0.87), post-contrast T1 (ICC=0.73) and T2bSSFP native T2 (ICC=0.88). Multimapping show high correlations with clinical reference mapping techniques for T1, T2 and ECV in a diverse cohort of patients with different cardiovascular diseases. Multimapping enables simultaneous T1 and T2 mapping and can be performed in a short breath-hold, with image quality superior to that of the clinical reference techniques.